Genetic Elucidation of Quorum Sensing and Cobamide Biosynthesis in Divergent Bacterial-Fungal Associations Across the Soil-Mangrove Root Interface - Zhou, Zhengyuan; Hu, Ruiwen; Ni, Yanmei; Zhuang, Wei; Luo, Zhiwen; Huang, Weiming; Yan, Qingyun; He, Zhili; Zhong, Qiuping; Wang, Cheng (Frontiers in Microbiology, 2021)
Plant roots in soil host a repertoire of bacteria and fungi, whose ecological interactions could improve their functions and plant performance. However, the potential microbial interactions and underlying mechanisms remain largely unknown across the soil-mangrove root interface. We herein analyzed microbial intra- and inter-domain network topologies, keystone taxa, and interaction-related genes across four compartments (non-rhizosphere, rhizosphere, episphere and endosphere) from a soil-mangrove root continuum, using amplicon and metagenome sequencing technologies. We found that both intra- and inter-domain networks displayed notable differences in the structure and topology across four compartments. Compared to three peripheral compartments, the endosphere was a distinctive compartment harboring more dense co-occurrences with a higher average connectivity in bacterial-fungal network (2.986) than in bacterial (2.628) or fungal network (2.419), which could be related to three bacterial keystone taxa (Vibrio, Anaerolineae and Desulfarculaceae) detected in the endosphere as they are known to intensify inter-domain associations with fungi and stimulate biofilm formation. In support of this finding, we also found that the genes involved in cell-cell communications by quorum sensing (rhlI, lasI, pqsH and lasR) and aerobic cobamide biosynthesis (cobG, cobF and cobA) were highly enriched in the endosphere, whereas anaerobic cobamide biosynthesis (encoded by cbiT and cbiE) was dominant in three peripheral compartments. Our results provide genetic evidence for the intensified bacterial-fungal associations of root endophytes, highlighting the critical role of the soil-root interface in structuring the microbial inter-domain associations.